Coating and Characterization of Mock and Explosive Materials. (7th August 2012) - Hunt, Emily M.; Jackson, Matt
Abstract : This project develops a method of manufacturing plastic-bonded explosives by using use precision control of agglomeration and coating of energetic powders. The energetic material coating process entails suspending either wet or dry energetic powders in a stream of inert gas and contacting the energetic powder with atomized droplets of a lacquer composed of binder and organic solvent. By using a high-velocity air stream to pneumatically convey the energetic powders and droplets of lacquer, the energetic powders are efficiently wetted while agglomerate drying begins almost immediately. The result is an energetic powder uniformly coated with binder, that is, a PBX, with a high bulk density suitable for pressing. Experiments have been conducted using mock explosive materials to examine coating effectiveness and density. Energetic materials are now being coated and will be tested both mechanically and thermally. This allows for a comprehensive comparison of the morphology and reactivity of the newly coated materials to previously manufactured materials.